Meningkatkan Pemahaman Konsep Fiqh melalui Pembelajaran Berbasis Masalah di MAN 3 Pekanbaru - Maryunis Maryunis (Milenial: Journal for Teachers and Learning, 2022)
This study aims to increase understanding of the concept of Fiqh through the application of problem-based learning at MAN 3 Pekanbaru. A good understanding of the concept of Fiqh is important for students to know and understand the teachings of Islam. Problem-based learning was chosen as an effective learning model to help students gain a deep understanding of Fiqh concepts. This study used a classroom action research method involving class X students at MAN 3 Pekanbaru. The stages of research include planning, implementation, observation, and reflection. In the planning stage, the researcher designs a problem-based learning plan that is relevant to the Fiqh concept to be studied. Then, the implementation phase involves the application of problem-based learning using case studies or real situations related to the concept of Fiqh. During the learning process, students will be actively involved in solving problems and implementing them the concept of Fiqh in the context of everyday life. The teacher will act as a facilitator who guides students in exploring problems, finding solutions, and formulating understanding of Fiqh concepts through discussion and collaboration in groups. The results of observation and evaluation were carried out to measure the increase in students' understanding after implementing problem-based learning. Tests, project assignments, and group discussions are used as evaluation instruments. Furthermore, the results of the evaluation are used as a basis for reflecting on and improving the problem-based learning strategy that has been implemented. It is hoped that this research can contribute to increasing students' understanding of Fiqh concepts at MAN 3 Pekanbaru through the application of problem-based learning. In addition, this research can also provide insights and recommendations to Fiqh teachers in developing more effective and relevant learning strategies.